Characteristics and Utilization of Long Wishkered Catfish (Mystus gulio) in Indonesia - Ayuningrum, Shima Bhaskara; Lubis, Friyuanita; Noordin, Harits (Universitas Teuku Umar, 2025)
Long-wishkered catfish is an Indonesian native species that can be found in the regions of Sumatra, Java and Kalimantan in rivers and estuaries. This study is based on a literature review containing the characteristics and uses of the Mystus genus of long wishkers catfish in Indonesia which was published in 2013-2023. There are 11 species of Indonesia`s native species which are included in the Mystus genus, one of which is the long wishkers catfish. This fish has barbels, a smooth body without scales and has a patil on the back. This fish is a micro carnivorous fish or crustacivores. There are partial spawners with fecundity ranging from 3100-24459 eggs. Currently, long wishkes catfish is widely used to make shrimp paste, salted fish and fish meal.